Skönlitteraturens språk - Christoffer Dahl; Anna Smedberg Bondesson (Educare)
This article explores the possibilities of combining literary and linguistic text analyses: a double perspective on the teacher education for secondary school. The aim is to analyze how two students, in a course in text analysis, solve an examination assignment where they are asked to combine literary and linguistic tools in their analysis of Pär Lagerkvist's short story "Father and I" (1924).  We ask the following questions: How do students use literary and linguistic tools in the analysis of Lagerkvist's work and how do they combine these tools? What kind of didactic potentials do students see in a double perspective? The result shows both similarities and differences in how the students combine linguistic and literary tools and how they underpin the analysis. The students’ meta-reflections indicate that such double perspective provides a deeper understanding of literary texts containing both literary and linguistic resources. Our conclusion is that the double perspective may provide a powerful theoretical and didactic tool for students of the Swedish language at the teacher education for secondary school.